2011
DOI: 10.1029/2011jd016282
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed ammonia emission from fumarolic vents associated with a hydrothermally active fault in the Salton Sea Geothermal Field, California

Abstract: Airborne hyperspectral imaging surveys were conducted over a geothermally active region straddling the southeastern shore of the Salton Sea in Southern California. The imagery was acquired across the 7.6–13.5 μm longwave‐infrared region with a ground sample distance of approximately 1 m. Prominent thermal hot spots associated with fumaroles along a known fault line were observed to coincide with emission of free ammonia, presumed to originate from geothermally induced pyrolytic decomposition of nitrogenous com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Two of the strongest anomalies highlight recently exposed fumarole fields near Mullet Island. The shape of the larger of these thermal anomalies agreed with the results from [29] who mapped it using 1 m spatial resolution SEBASS data. Many of the nearly twenty individual geothermal features noted by [27] (squares in Figure 9c) are small or not very active.…”
Section: Tir Data For Thermal Anomaly Identificationsupporting
confidence: 81%
See 2 more Smart Citations
“…Two of the strongest anomalies highlight recently exposed fumarole fields near Mullet Island. The shape of the larger of these thermal anomalies agreed with the results from [29] who mapped it using 1 m spatial resolution SEBASS data. Many of the nearly twenty individual geothermal features noted by [27] (squares in Figure 9c) are small or not very active.…”
Section: Tir Data For Thermal Anomaly Identificationsupporting
confidence: 81%
“…The Mullet Island and Wister fumarole fields define lineaments interpreted to be the Calipatria Fault [26] and an extension of the San Andreas Fault [27], respectively. Reath and Ramsey [28] used airborne Spatially Enhanced Broadband Array Spectrograph System (SEBASS) data (7.6-13.5 µm) data to map geothermal indicator minerals in this region, and Tratt et al [29] used SEBASS data to map ammonia plumes and surface temperature. Ammonia emissions are likely derived from geothermal fluids moving through decomposing agricultural runoff and organic material [29].…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-sectional flux method as discussed by Varon et al (2018) is an established tool for airborne in-situ observations (White et al, 1976;Mays et al, 2009;Cambaliza et al, 2014Cambaliza et al, , 2015Conley et al, 2016). It has also been applied to airborne CH 4 (partial) column measurements (Krings et al, 2011(Krings et al, , 2013Tratt et al, 2011Tratt et al, , 2014Amediek et al, 2017). Based on the mass balance assumption, the strength Q of a CH 4 point source such as a coal mine ventilation shaft can be calculated by 5 integrating the product of CH 4 concentration enhancements and wind speed along a plume cross-section.…”
Section: Cross-sectional Flux Methodsmentioning
confidence: 99%
“…Nevertheless, HSI can map surface composition with broadband absorption features to identify different minerals [Kruse et al, 1993] and rapidly collect spatial data. Recent HSI measurements in the shortwave infrared (SWIR) [Roberts et al, 2010] and TIR [Tratt et al, 2011] have demonstrated the value of high spatial resolution (subdecameter) information for detecting and mapping trace gas anomalies such as plumes, using diagnostic spectral features. We propose that combined TIR/ SWIR trace gas remote sensing provides synergies that justify leveraging the information from these different spectral regimes.…”
mentioning
confidence: 99%